Information Behaviour of Juvenile Delinquents at Adigbe Borstal Training Institution in Abeokuta Metropolis - Adegbaye, Sarah Irherhimena (Communicate: Journal of Library and Information Science, 2023)
This paper investigates information behaviour of Juvenile delinquents at Adigbe Borstal Training Institution in Abeokuta Metropolis. The study employs survey research design, with a questionnaire serving as the main research instrument, supplemented with interview, observation and secondary document reviews. Seventy (70) juvenile delinquents participated in the study out of the one hundred and forty-six (146) juveniles in conflict with the law. Out of the seventy (70) copies of questionnaire administered, 65 were returned and found usable. The data was analysed using descriptive statistics. Findings revealed that juvenile delinquents needed information on how to leave the facility, family and social service, legal rights information, health information, societal information, and personal development information. These juvenile delinquents mostly sourced their needed information from clerics visiting the facility, counsellors/social workers, guest speakers, workshops, books, and the library. Finding revealed that most juvenile offenders were not satisfied with the information they received. Surprisingly, the inmates claimed the information they accessed in the home are useful to their rehabilitation process. The challenges to access to information identified in this study include fear, experiences of stigmatisation and judgment, absence of guidance or support, lack of confidence, and limited access to computer and internet. The outcome of this study contributes to the scarce literature on information behaviour of juvenile offenders in Borstal institutions in Nigeria.